Maz̤āmīn-i Cakbast : Panḍit Brij Narāʼin Cakbast Lakhnavī ke maz̤āmīn kā majmūʻah - Cakbast, Brij Narāʼin, 1882-1926 (SAMP early 20th-century Indian books project ;, 1928)
Literary and critical articles with reference to Urdu.